The Canacidae of the Arabian Peninsula (Diptera: Brachycera: Carnoidea) - Munari, Lorenzo (Zootaxa, 2016)
A review of the canacid fauna of the Arabian Peninsula is provided. In addition to the usual taxonomic account, a key to all genera and species is also provided. Many figures illustrate some of the main characters that will hopefully be useful for identifying some taxonomically difficult species.